Adolescents with and without idiopathic scoliosis have similar self-reported level of physical activity: a cross-sectional study. Issue 1 (December 2016) - Diarbakerli, Elias; Grauers, Anna; Möller, Hans; Abbott, Allan; Gerdhem, Paul
Abstract Background Little is known about physical activity levels in individuals with idiopathic scoliosis. The aim of this study was to describe the level of physical activity in adolescents with and without idiopathic scoliosis. Methods Two hundred thirty-nine adolescents, median (25th, 75th percentile) age 16.0 (14.4, 17.6) with idiopathic scoliosis and 58 randomly recruited population-based individuals without scoliosis aged 14.6 (12.8, 16.3) participated. The 239 idiopathic scoliosis patients consisted of 88 untreated, 43 previously braced, 36 with ongoing brace-treatment and 72 surgically treated individuals. Main outcome measure was the proportion achieving at least moderate activity level, as estimated by the International Physical Activity Questionnaire short form (IPAQ-SF). Other outcome measures were Metabolic Equivalent Task (MET) minutes/week, time spent sitting, spare time activity level and sporting activities. Statistical analyses were adjusted for age and sex. Results The proportion of individuals with scoliosis with moderate activity level was 180 out of 239 (75 %) and for individuals without scoliosis 49 out of 58 (85 %) (p  = 0.14). Median MET-minutes/week (25th, 75th percentile) was for individuals with scoliosis scoliosis 1977 (840, 3777) and for individuals without scoliosis 2120 (887, 4598) (p  = 0.11). Sporting activities did not differ (p  = 0.28). The ongoing brace-treatment group had a significantly higher proportion of individuals categorizing themselves at high spare time activity level compared to the surgically treated and previously braced individuals (p  = 0.046). No difference was seen between the treatment groups regarding the proportion achieving moderate activity (p  = 0.11) and sporting activities (p  = 0.20). Median MET minutes/week was 2160 (794, 3797) for the untreated group, 989 (661, 2706) for the previously braced group, 2055 (1010, 4026) for the surgery group and 2106 (990, 4480) for the ongoing brace-treatment group (p  = 0.031). Conclusion Adolescents with idiopathic scoliosis show similar levels of self-reported physical activity as individuals without idiopathic scoliosis. Bracing and surgery do not appear to inhibit physical activity.